STRATEGI PEMASARAN BERKELANJUTAN DAN PERENCANAAN JANGKA PANJANG DALAM MENINGKATKAN DAYA SAING PADA PROGRAM STUDI MAGISTER MANAJEMEN UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA - Reza Alkautsar; Khoirul Anam (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
Sustainable marketing is a marketing strategy that is oriented towards environmental and social sustainability. This strategy is important in improving the competitiveness of a study programme, including the Master of Management Study Programme of Marshal Suryadarma Aerospace University (Elemenya). This research aims to analyse the sustainable marketing strategy and long-term planning in improving the competitiveness of the Elementya Master of Management Study Program. This research uses a qualitative method with a case study approach. Research data were obtained through in-depth interviews with resource persons consisting of the leadership of Elementya, the leadership of the Elementya Master of Management Study Programme, and alumni of the Elementya Master of Management Study Programme. The results showed that the Elementya Master of Management Study Programme has implemented a sustainable marketing strategy which includes: (1) development of a sustainability-oriented curriculum, (2) organising sustainability activities, and (3) cooperation with partners committed to sustainability. This sustainable marketing strategy has had a positive impact on the competitiveness of the Elementya Master of Management Study Programme, namely: (1) increased reputation and public trust, (2) increased number of applicants, and (3) improved quality of graduates. This research provides recommendations for the Elementya Master of Management Study Programme to continue to strengthen its sustainable marketing strategy, as well as improve the synergy between sustainable marketing strategies and long-term planning.